Light-front quark model consistent with Drell-Yan-West duality and quark counting rules; Physical Review D; Vol. 89, iss. 5 - Gutsch Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Nagy Miroslav; Schmidt I.; Vega A. (2015, 2015)
Title screen